Otologic assessment of blast and nonblast injury in returning middle east‐deployed service members. (17th May 2013) - Shah, Anil; Ayala, Marco; Capra, Gregory; Fox, David; Hoffer, Michael
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To determine if tympanic membrane perforation offers any protection from inner ear damage and determine the incidence and pattern of otologic blast injury in military personnel returning from deployment. Study Design Retrospective analysis of US service members injured in Operation Iraqi Freedom and Operation Enduring Freedom from October 2006 to October 2007. Methods One‐hundred ten blast‐injured patients were compared to 54 nonblast‐injured patients returning from deployment. Data captured included audiogram results, presence of tympanic membrane perforation, demographic data, location and nature of injury, loss of consciousness, sleep disturbance, confusion, and symptoms of headache, dizziness, memory loss, and tinnitus. Results Of 110 blast‐injured patients, 18 patients suffered tympanic membrane perforation (16%), of which nine patients suffered bilateral tympanic membrane perforation (8%). Blast patients suffered more hearing loss than controls as measured by pure‐tone averages of varying speech reception frequencies and at 6, 000 Hz. Of the blast patients who recorded an audiogram, nearly 24% suffered moderate to profound hearing loss. There was no statistically significant difference in hearing outcomes between blast‐injured patients with tympanic membrane perforations and those without; however, when comparing patients with unilateral perforations with their contralateral ear, there was a difference in hearing thresholds at 6, 000 Hz. There was a significantly increased risk of tinnitus, memory loss, headache, and dizziness between blast‐injured patients compared to controls. Conclusions Due to its violent nature, blast exposure causes greater neuro‐otological manifestations and deserves prompt otologic evaluation. Level of Evidence 3b. Laryngoscope, 124:272–277, 2014